Growth Hormone and the Lipolysis of Exercise (Res Medica, 2014)
From a dissertation read before the Society on January 22nd. 1969.Growth hormone (GH) is secreted by the acidophil cells of the anterior pituitary. It is a protein, partially α-helix in structure, of molecular weight 29,000 in man (1 ). In addition to its effect in promoting growth several metabolic effects follow its administration, one of which, the mobilisation of free fatty acid (FFA) from adipose tissue, will be discussed in some detail.The radio-immunoassay methods for estimating GH (2, 3) which are the most sensitive and accurate now available, depend on the fact that radio-iodinated GH of high specific activity (4) competes with standard or test GH in plasma for binding sites on a  γ-globulin in antiserum prepared in rabbits. The competition results in ‘bound’ and ‘free’ 131I-GH which are separable electrophoretically and counted for radio-activity. Inhibition curves relating bound: free ratios to standards are drawn and test samples assayed against them.There is good evidence that the assay is specific (5). Reactive material is elevated in acromegaly and is absent after hypophysectomy: jugular vein plasma contains more than inferior vena cava plasma: cross-reaction occurs between plasma samples only from species whose pituitaries contain cross-reactive material: acromegalic plasma acts just as a plasma dilution of pituitary extract.